Participating in sports and practicing a religion are related to levels of happiness - Tejero-González Carlos Mª (Sciendo, 2020)
The objective of this study was to ascertain whether happiness varies depending on sports participation and religious practice. The sample comprised 2,378 participants aged between 18 and 92 years. All analysis were carried out by testing the interaction effects of the variables of sex and age on sports participation, religious practice, and happiness. We found a high average level of happiness (M = 7.299, range 0-10). However, people who do not participate in sports or practice a religion indicated a level of happiness (M = 6.979) that was statistically lower than that of the other groups: people who practice a religion but do not participate in sports (M = 7.135); people who participate in sports but do not practice a religion (M = 7.478); and people who both participate in sports and practice a religion (M = 7.717). We conclude that happiness is associated with sports participation and religious practice, although with small or very small effect sizes (all p< 0.050; η2p between 0.008 and 0.020).